EFEKTIVITAS DIKLAT DASAR PENYULUH PERTANIAN AHLI SWADAYA DI UPTD BALAI PELATIHAN DAN PENYULUHAN PROVINSI BENGKULU TAHUN 2022 - Muhammad Ali Hanafiah; Annastasia Surbakti; Riadi Tarigan (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The Basic Training of Expert Agricultural Extension is carried out in order to equalize perceptions of the main tasks and functions, develop comprehensive insights into thinking and increase competence and professionalism for Agricultural Extension Workers. However, in reality the implementation of education and training sometimes does not achieve the goals set. Implementation of education and training is often stuck in the routine of annual activities. The purpose of this study was to analyze the level of effectiveness of the Basic Agricultural Extension Training of Self-Help Experts, at the level of reaction and learning as well as the factors that influence it. The sampling technique used was a census with 29 respondents. The increase in training participants' knowledge is calculated from the difference between the post-test minus the pre-test, then analyzed using a pair sample t-test. To find out the factors that influence the effectiveness of the training, statistical tests were carried out using multiple regression analysis. The results showed that the level of effectiveness of basic self-help agricultural extension training was in the good category. Material quality, training methods, training facilities, widyaiswara competence, time management and committees simultaneously affect the effectiveness of the training, however partially only the competence of the widyaiswara and time management affect the effectiveness of the training.